2018
DOI: 10.21059/buletinpeternak.v42i1.23317
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lactic Acid Bacteria as Ruminant Probiotic Candidates Based on In Vitro Rumen Fermentation Characteristics

Abstract: This research was conducted to select, to identify LAB isolates and to investigate the effects of the LAB as probiotics candidate in the rumen fermentation. Nine isolates exhibited the potency as candidate probiotics for cattle. The experiment was arranged in randomized block design with ten treatments and three different times of in vitro as a block. The substrate consisted of 70% forage and 30% concentrate proportion. The substrate was incubated at 39oC using serum bottle of 100 ml capacity for fermentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Our results agree with Ridwan et al . (2018) who reported that the amount of GP, values of b and the values of c have increased as a result of supplementing the diet with 8 LP strains compared with the nonadditive treatment. Furthermore, Elghandour et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with Ridwan et al . (2018) who reported that the amount of GP, values of b and the values of c have increased as a result of supplementing the diet with 8 LP strains compared with the nonadditive treatment. Furthermore, Elghandour et al .…”
Section: Discussionmentioning
confidence: 99%
“…All the concentrations of probiotics had higher percentage of digestibility than the control (P = .05). The digestibility of A1D42 at 4x10 13 UFC/g concentrations had the greatest digestibility (66%), but it was no different with the A1D42 4x10 12 (Fig. 2).…”
Section: Digestibility Of the Lyophilized Probioticmentioning
confidence: 93%
“…Each digestion vessel received ten bags, 1600 mL (5:1) of the buffer solution, 400 mL of ruminal fluid and the probiotic at doses 4X10 11 , 4X10 12 and 4X10 13 UFC/g were added; the vessels were injected with CO 2 , and were positioned in the DAISY II digestor at 39 ºC for 48 h rotating. After that, the bags were washed, dried and were weighted to calculate the digestibility.…”
Section: Digestibility Of the Lyophilized Probioticmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms such as Lactobacillus, Streptococcus and Enterococcus are among the commonly used probiotics for ruminants (Seo et al, 2010). Ridwan et al (2018) reported that L. plantarum strain 32 isolated from cow rumen had higher in vitro dry matter and organic matter digestibilities and overall production of gas in comparison with the control. Oyeleke and Okusanmi (2008) stated that P. aeruginosa inhabited the rumen of cows, sheep, and goats and could hydrolyse cellulose.…”
Section: Introductionmentioning
confidence: 99%